Enhanced Mucosal Defense and Reduced Tumor Burden in Mice with the Compromised Negative Regulator IRAK-M - Daniel E. Rothschild; Yao Zhang; Na Diao; Christina K. Lee; Keqiang Chen; Clayton C. Caswell; Daniel J. Slade; Richard F. Helm; Tanya LeRoith; Liwu Li; Irving C. Allen (EBioMedicine, 2017)
Aberrant inflammation is a hallmark of inflammatory bowel disease (IBD) and colorectal cancer. IRAK-M is a critical negative regulator of TLR signaling and overzealous inflammation. Here we utilize data from human studies and Irak-m−/− mice to elucidate the role of IRAK-M in the modulation of gastrointestinal immune system homeostasis. In human patients, IRAK-M expression is up-regulated during IBD and colorectal cancer. Further functional studies in mice revealed that Irak-m−/− animals are protected against colitis and colitis associated tumorigenesis. Mechanistically, our data revealed that the gastrointestinal immune system of Irak-m−/− mice is highly efficient at eliminating microbial translocation following epithelial barrier damage. This attenuation of pathogenesis is associated with expanded areas of gastrointestinal associated lymphoid tissue (GALT), increased neutrophil migration, and enhanced T-cell recruitment. Further evaluation of Irak-m−/− mice revealed a splice variant that robustly activates NF-κB signaling. Together, these data identify IRAK-M as a potential target for future therapeutic intervention.